Symptomatic Vocabulary with Built-in Emotion - Evgenia R. Ioanesyan (Научный диалог)
The analysis of symptomatic vocabulary - units denoting a person’s reaction to a certain emotion or the state of a person who is in the grip of emotion is considered in the article. Two classes of symptomatic units are given: (1) units describing the uncontrolled physiological reactions of a person to emotion, for example, blush with embarrassment, pleasure ; (2) units that describe mental signs that indicate a change in a person’s normal behavior under the influence of strong emotion, for example, to go crazy with fear or jealousy . The focus is on a subclass of symptomatic vocabulary - symptomatic units with built-in emotion. The peculiarity of these units is that they reflect the conceptualization of emotion through a symptom that correlates with this emotion in the picture of the world of a particular language. For example, the verb blush in metaphorical use means a sense of shame ( blush for your actions, for your son ); the French noun stupeur stupor, numbness’ acts as a unit with built-in emotion, indicating a strong surprise. The relevance of the study is determined by the fact that the analysis of symptomatic expressions, especially symptomatic vocabulary with built-in emotion, allows you to identify differences in the conceptualization of emotions in different languages.